HUBUNGAN KETEBALAN LEMAK TERHADAP RUNNING SPEED PADA PEMAIN SEPAK BOLA LAKI-LAKI AMATIR - Octaviani Paquita Tarigan (2021)
Football is one of the most popular sports in the world and can be played by both men and women. Football has important components that must be considered, one of which is anthropometry and running speed. Anthropometry is divided into several types, namely weight, length, circumference and fat thickness. Mormal or excess fat thickness in soccer player can affect the speed when playing, making soccer players uncomfortable when competing. This study aims to determine the relationship between fat thickness and running speed in amateur male soccer players. The type of research design used is a cross-sectional study with 24 mal respondents aged 20-27 years and conducted by observation. The parameters use to find the relationship between fat thicknss and running speed are the skinfold caliper and the 30 meter sprint test. Based on the results of 24 respondents, the highest fat thickness value was in the moderate category with a percentage of 29.2% and the highest running speed value was in the moderate category with a percentage of 41.7%. After the correlation test, it was found that there was a relationship between fat thickness and running speed, Spearman's rho correlation coefficient p= 0.443 in the same direction. The conclusion of this study resulted that fat thickness had an affect on running speed.